THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK ENVIRONMENT, AND LEADERSHIP ON EMPLOYEE PERFORMANCE IN THE PUBLIC SECTOR - Yanuaria Jeniyanti Bita Seran; Elevenson Nadapdap; Umu Khouroh; Yusaq Tomo Ardianto (Adisam Publisher, 2025)
This study investigates the influence of organizational culture, work environment, and leadership on employee performance within the Regional Secretariat of Malaka Regency, Indonesia. Employing a quantitative approach with a causal research design, data were collected from 139 civil servants using a structured questionnaire. The data were analyzed using multiple linear regression. The findings reveal that both organizational culture and work environment have a significant positive impact on employee performance, particularly when they foster innovation, transparency, and collaboration. Leadership also demonstrates a positive effect, although to a lesser extent compared to the other two variables. The combined effect of the three independent variables accounts for 49.7% of the variation in employee performance. This study provides practical implications for public sector management by emphasizing the need to strengthen organizational culture, create a supportive and conducive work environment, and enhance leadership effectiveness. The findings also contribute to the broader literature on human resource management in government institutions, particularly in emerging economies.